Apakah Parousia Ditunda? - Jahotner F. Manullang (Fakultas Filsafat Universitas Advent Indonesia, 2013)
The people of God in the last days are waiting for the fulfillment of the promise of Christ's second coming. But until now that promise has not materialized. Is parousia being delayed? Or whether God’s people misinterpret it? Or whether Christ erred in giving that promise? This study describes the nature of parousia according to the Bible and the writings of Ellen G. White, balanced and complete.